Kadar N, P Daun dan Produksi Kelapa Sawit Melalui Penempatan TKKS Pada Rorak - Juliana Hannum; Chairani Hannum; Jonatan Ginting (Universitas Sumatera Utara, 2014)
The objectives of this research was to study effect of aplication empty fruit bunches oil palm andconcentrated flow areas depth treatment on N, P leaf nutrient content and production. The researchwas conducted in Afdeling II, at block F17, PTPN III Kebun Bangun, Simalungun, NorthSumatera, from July to October 2013, used factorial randomized block design with two factors and3 replication. The first factor was aplication empty fruit bunches oil palm were 0, 200 kg, 250 kg,300 kg. The second factor was concentrated flow areas depth were 40 cm, 60 cm, 80 cm. The resultof this research showed that aplication empty fruit bunches oil palm increase P leaves content butnot significant effect N leave content, and production. Concentrated flow areas depth treatment hasnot significant effect N, P leaves content and production. Interaction of EFBOP treatment andconcentrated flow areas depth increase P leaves content but not significant effect on N leavescontent and production.Keywords: EFBOP, concentrated flow areas, N leaves content, P leaves content, oil palm